2016
DOI: 10.1016/j.forpol.2016.05.021
|View full text |Cite
|
Sign up to set email alerts
|

The role of institutions in the production of space for tourism: National Forest Parks in China

Abstract: Nature-based tourism is a global phenomenon, with traditional forms of use of natural areas, such as wood harvesting and agriculture, paving the way for ecotourism. However, there has been limited exploration of the role of institutions in driving this transition. Consequently, this paper sought to explore the role of institutions in producing space for tourism within National Forest Parks (NFPs) in China. To achieve this objective 68 nationallevel policy documents from 1949 to 2014 were collected and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The second one is the style of traditional landscape drawings as the Eastern landscape painting adopts various viewing points and is good at combining the foreground and background to depict beautiful rural landscapes [8,14]. The third one is the cognition of the forest's value attribute, as according to the cognitive conception, the feature of the forest as the space for timber production is more often emphasized so as to highlight the natural attribute, while that of the forest as the space for the supply of public ecological products is neglected, which reduces the social attribute of the interaction between the forest and people [18]. Researches have shown that the public of Russia prefer the natural resources so prominently that they use mushrooms and berries as featured landscape elements to indicate that the forest is an important space for resources of traditional living materials;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second one is the style of traditional landscape drawings as the Eastern landscape painting adopts various viewing points and is good at combining the foreground and background to depict beautiful rural landscapes [8,14]. The third one is the cognition of the forest's value attribute, as according to the cognitive conception, the feature of the forest as the space for timber production is more often emphasized so as to highlight the natural attribute, while that of the forest as the space for the supply of public ecological products is neglected, which reduces the social attribute of the interaction between the forest and people [18]. Researches have shown that the public of Russia prefer the natural resources so prominently that they use mushrooms and berries as featured landscape elements to indicate that the forest is an important space for resources of traditional living materials;…”
Section: Discussionmentioning
confidence: 99%
“…The research primarily uses quantitative research methods, such as the photo grading method [9], the method of semantic differential [10], the Delphi method [11], the field interview [12], the landscape image sketching technique [13], and the creation of multidimensional cognition and value evaluation models [14,15]. The study of China's scholars on the perception of forests mainly concentrates on the forest aesthetics [16], the forest landscape quality evaluation [17], the exploration of multi properties of forests [18], etc., and the methods often used to create the evaluation system of in-forest landscapes or to evaluate the quality of the in-forest landscapes include the Analytic Hierarchy Process (AHP) [19], the Analytic Network Process (ANP) [20], and the Scenic Beauty Assessment Method (SEB) [21], etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, foreign institutional ownership is not influenced by the proportion of independent directors. Luo, Moyle, Bao, et al [45] examined the role of institutions in generating areas for tourism in national forest parks and showed how institutional changes reflect the dynamic role of the state, capital, and society in China's national forest parks.…”
Section: Brief Literature Review On Institutional Quality and Tourismmentioning
confidence: 99%
“…Other researches linked the theory to the concept of public space, such as the production of public space in the City of Manchester, England (Leary, 2013); post-industrial space production in Rotterdam, the Netherlands (van den Berg & Chevalier, 2018); public space in Brisbane Australia (Zamanifard et al, 2018) and the emancipatory feminism movement in Utah USA (Nicolosi, 2020) The study of Lefebvre's space production had been examined from several aspects. For example, the tourism aspect: the Chinese National Forest Park (F. Luo et al, 2016); and the Yamal Peninsula, Northern Siberia, Russia (Gorbuntsova et al, 2019). From education and professional aspect, researches have been done on the academic socialisation as the production and negotiation of social spaces in New Zealand (Soltani, 2018) and the production of shared workspaces in Shenzhen, China (Y.…”
Section: Introductionmentioning
confidence: 99%